Quantification and pharmacokinetics of Taiwanin E methyl ether in rats by liquid chromatography–tandem mass spectrometry. (15th June 2012) - Qiu, Feng; Fu, Shujun; Zhou, Shujun; Yang, Shihai; Yang, Meihua
ABSTRACT This study firstly describes the development of an accurate and sensitive high‐performance liquid chromatography–tandem mass spectrometry (LC‐MS/MS) assay for the quantification of Taiwanin E methyl ether (TEME) in rat plasma. The assay involved a simple liquid–liquid extraction step with ethyl acetate and a gradient elution using a mobile phase consisting of water containing 0.1% formic acid and acetonitrile containing 0.1% formic acid. Chromatographic separation was successfully achieved on an Agilent Zorbax‐C18 column (2.1 × 50 mm, 3.5 µm) with a flow rate of 0.40 mL/min. The multiple reaction monitoring was based on the transitions of m/z = 379.1 → 320.1 for TEME and 386.1 → 122.0 for buspirone (internal standard). The assay was validated to demonstrate the specificity, linearity, recovery, accuracy, precision and stability. The lower limit of quantification was 0.50 ng/mL in 50 μL of rat plasma. The developed and validated method was successfully applied to the quantification and pharmacokinetic study of TEME in rats after intravenous and oral administration of 1.45 mg/kg TEME. The oral absolute bioavailability of TEME was estimated to be 5.85 ± 1.41% with an elimination half‐life value of 2.61 ± 0.55 h, suggesting its poor absorption and/or strong metabolism in vivo. Copyright © 2012 John Wiley & Sons, Ltd.